Implementasi Program Anti Bullying dalam Upaya Mewujudkan Sekolah Ramah Anak - Ariyanta, Dafid; YSH, AY Soegeng; Maryanto, Maryanto (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The child-friendly school program is one of the policies in an effort to provide solutions on how to create schools that are safe, comfortable and enjoyable for children. The aim of the research is 1) to find out and analyze anti-bullying program planning in an effort to create child-friendly schools. 2) to find out and analyze anti-bullying program organizers in an effort to create child-friendly schools. 3) to find out and analyze the implementation of anti-bullying programs in an effort to create child-friendly schools. 4) to find out and analyze the supervision of the anti-bullying program in an effort to create a child-friendly school at SMA Negeri 1 Pecangaan, Jepara Regency. The research approach used is qualitative. This type of research is a case study. Qualitative research design through 1) pre-field or orientation stage, 2) fieldwork or focused exploration stage, 3) data analysis. Data collection techniques are interviews, observation and documentation. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The results of the research show that: 1) planning by conducting a needs analysis, forming a child-friendly school team, compiling a child-friendly anti-bullying school program, determining program priorities and socializing anti-bullying programs in child-friendly schools. 2) organizing by placing school resources, organizational development, assignment and delegation of authority. 3) Implementation of procedures for directing and providing motivation to all school members, child-friendly school policies by implementing 3P (provision, protection and participation) rules, formation of an anti-bullying task force, anti-bullying SOPs. 4). The evaluation was carried out by evaluating the school's internal team and the joint team of Cluster 4 of the KLA Task Force. The school principal followed up by holding discussions and communication, deliberating together. The author suggests that school principals and teachers, as the main actors in this activity, must always collaborate starting from planning, implementation, to evaluation. Keywords: Implementation, Anti-Bullying, Friendly School